Comparative benchmark analysis of coverage by specialists involved in healthcare provision to patients with cardiovascular diseases in the regions of the Northwestern Federal District - G. A. Neplyueva; A. E. Solovieva; V. V. Zaitsev; N. G. Avdonina; A. V. Bespalov; G. V. Endubaeva; A. A. Fedorenko; A. N. Yakovlev; N. E. Zvartau; A. O. Konradi; S. V. Villevalde (Российский кардиологический журнал, 2022)
Control of cardiovascular diseases  (CVDs), which are the cause of premature mortality and high economic  costs,  is one of the priorities of social policy. Human resources are a key link in health system performance.  In Russia, there is a significant geographical  heterogeneity  in the distribution of medical workers and structural disproportions  in certain specialties.  Regional  differences  in the availability of specialists in cardiology system have not been studied enough.Aim. To perform a comparative benchmark analysis of coverage by specialists involved  in healthcare  provision  to patients with cardiovascular  diseases  in the regions of the Northwestern Federal District (NWFD), identifying regional differences for the period from 2015 to 2019.Material and methods. To assess the number of specialists involved in providing care to patients with CVDs, data from the federal statistical monitoring forms №30 “Information on a medical organization” for 2015-2019 of the subjects of the Northwestern Federal District were used. Multiple linear regression was used to compare the basic estimated parameters of provision per 10000 population with specialists at the level of district as a whole and in NWFD regions  with data for Russia as a whole. P<0,05 was considered significant.Results. Among the subjects of Northwestern Federal District, differences  were revealed  in all specialties  of varying severity. While the estimated parameter of provision with cardiologists  in Russia is 0,896 (95%  CI, 0,794-0,998),  there are differences  in the regions in a wide range from -0,446 (Vologda Oblast) to +0,502 (St. Petersburg).  Regional  differences  in the provision of vascular radiology specialists from the basic estimated level for Russia were observed  only in two subjects. At the same time, for all subjects in general, an increase in the indicator from 2015 to 2019 by 0,011 [95% CI, 0,006; 0,016] per year (p<0,001) was observed.  The smallest range of differences was observed for cardiovascular surgeons:  with a baseline  estimate  in Russia of 0,158 [95% CI, 0,140; 0,176] the range of differences was from -0,086 to +0,198. For emergency  medicine paramedic, the largest number of subjects with positive values of the statistical correction of the average relative to Russia was noted (7 out of 11 regions). For neurologists and intensivists, on the contrary, the largest number of subjects with negative values (7 out of 11 regions)  was revealed.  Structural staff disproportions in cardiology care system were revealed.Conclusion. In the NWFD, in general, coverage  by specialists involved in health-care provision for CVD are higher than the estimated base level for Russia. However,  their uneven distribution within the district and its subjects is observed. The demonstrated mathematical approach to assessing staff differences  at the subject or district level can be used to develop measures to achieve the goals of the regional health personnel policy.